Caves - Beckerman, Nell Cross, 1973-; Chock, Kalen (New York : Orchard Books, an imprint of Scholastic, 2022)
"A masterful exploration of one of nature's most curious ecosystems, Caves is a magical journey into subterranean wonders perfect for fans of Jason Chin. Using evocative storytelling, Nell Cross Beckerman urges children to explore one of nature's most curious ecosystems. Dramatic, poetic language guides kids through different caves around the world while nonfiction text allows for deeper understanding"--.
new kids book 2023 spring.
Ages 4-8.
Grades K-1.
Keywords: Caves -- Juvenile literature; Speleology -- Juvenile literature